Development of instant appam mix supplemented with millet and legume flour - Zalate, S T; Balwan, D S; Vasawade, S A; Yadav, D N; Patil, S N; Jamdar, J L (Journal of Postharvest Technology, 2023)
One of the most consumed fermented morning foods in South India and Sri Lanka is appam. Commercially produced dry ingredient mixtures known as "instant mixes" that are quick and simple to manufacture. By considering present population increasing demand for a healthy, simple and convenient foods, the present investigations was carried out to formulate pearl millet, soybean supplemented instant appam mix in four different proportions. Sample A, B, C and D were formulated which contain rice flour, black gram flour along with pearl millet flour, and soya flour in different levels. It was found that organoleptic evaluation of sample C formulation had scored highest in texture (7.9), overall acceptability (8.3) and taste (8.1). The most acceptable instant appam mix sample was further analyzed for their nutritional composition and shelf life study. Nutritional properties showed that sample C formulation had protein (15.3 %), carbohydrates (66.7%) and crude fiber (5.52 %). Storage studies have showed that appam prepared from sample C stored for 5 months were found acceptable up to 150 days of storage. It may be concluded that instant appam mix could be stored up to 5 months successfully without any significant change in their sensory attributes.